2015
DOI: 10.5005/jp-journals-10024-1783
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Transportation by Comparing Several uses of Rotary Endodontic Files

Abstract: ProTaper Next nickel-titanium (NiTi) file system is a safe instrument that respects the canal shape, allows practitioners to treat difficult cases with good results, and low risk of separation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Because root canal instruments are tapered and therefore stiffer in direction of the shaft, more transportation will result in cases with more coronally located curvatures. In the literature, many studies can be found in which root canal instruments were tested in simulated root canals [ 1 , 7 9 , 11 , 14 16 , 18 ]. Clear resin blocks are therefore a widely used method that is thought to be highly reproducible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because root canal instruments are tapered and therefore stiffer in direction of the shaft, more transportation will result in cases with more coronally located curvatures. In the literature, many studies can be found in which root canal instruments were tested in simulated root canals [ 1 , 7 9 , 11 , 14 16 , 18 ]. Clear resin blocks are therefore a widely used method that is thought to be highly reproducible.…”
Section: Discussionmentioning
confidence: 99%
“…There is no standard protocol to compare the shaping ability of different root canal instruments in a reproducible way, even though there are plenty of publications describing different in-vitro methods to evaluate such instruments [ 1 14 ]. These publications can be divided into publications performed on extracted teeth [ 2 6 , 10 , 12 , 13 ] or on simulated root canals in resin blocks [ 1 , 7 9 , 11 , 14 , 15 ]. While some researchers advocated root canals in extracted teeth for the more realistic situation with natural dentine properties [ 16 ], others advocated the advantage of high standardization of simulated artificial root canals [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%